2022
DOI: 10.1039/d2ay01520j
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the performance of cross-linked poly(acrylic acid) and poly(methacrylic acid) as efficient adsorbents in SPE columns for simultaneous preconcentration of tricyclic antidepressants in water samples

Abstract: A solid phase extraction-based (SPE) procedure for simultaneous preconcentration of five tricyclic antidepressants (TCAs), amitriptyline hydrochloride (AMT), nortriptyline hydrochloride (NOR), doxepin hydrochloride (DOX), imipramine hydrochloride (IMI), and clomipramine hydrochloride (CLO)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…48,49 IMH, a TCA, is a potent norepinephrine nerve terminal reuptake inhibitor, and studies confirmed the presence of such drugs in rivers and oceans and their deleterious impact on human and aquatic life. 50,51 Based on that, it is imperative to establish a rapid and accurate detection method for BPA/IMH. Recently, fluorescence detection methods have seen extensive use, due to their simple preparation process and high sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…48,49 IMH, a TCA, is a potent norepinephrine nerve terminal reuptake inhibitor, and studies confirmed the presence of such drugs in rivers and oceans and their deleterious impact on human and aquatic life. 50,51 Based on that, it is imperative to establish a rapid and accurate detection method for BPA/IMH. Recently, fluorescence detection methods have seen extensive use, due to their simple preparation process and high sensitivity.…”
Section: Introductionmentioning
confidence: 99%